Correlation in Between Inhibition Efficiencies and Stability Constants of The Schiff Bases and Their Metal Complexes - Sari, Nursen; Aytac, Aylin (Asian Journal of Chemistry, 2010)
To investigate the relationship between corrosion inhibition and formation constants of -Cl and -OCH3 substituted 2-aminophenol Schiff bases and their Cu(II), Co(II) and Ni(II) complexes have been synthesized. Inhibitor effect of synthesized Schiff bases and their complexes, as corrosion inhibitors for aluminium in 0.1 M HCl, have been determined by potentiodynamic polarization and impedance techniques. The inhibition efficiencies obtained Tafel plots and EIS methods are in good agreement. The protonation constants of the Schiff bases and stability constants of the metal complexes have been determined potentiometrically in 1:1 methanol:water solution at 25 ºC and 0.1 M KCl ionic strength. In this study, it seems that the Cu(II) complex has highest formation constants and is best inhibitor for Al alloy in 0.1 M HCl.